Tinjauan Nahdlatul Ulama dan Muhammadiyah dalam Melihat Hukum Bunga Bank - Mahtumah (Asy-Syari’ah : Jurnal Hukum Islam, 2016)
Economic activity from time to time had been developed, which used to exist now did not exist, or vice versa. First institutional investors such as banks are not known and there is now. Then a new problem in fiqh muamalah arises when faced with the problem of understanding usury banks. On the one hand, interest rates (bank interest) trapped in riba criteria, on the other hand, the bank has a large social function, it can be said without bank of a country will be destroyed. Financial system and the economic relations these days, both within and outside the country, is through the bank channel. No one any country that does not have a company bank, because banks can launch any nexus and ensure the survival of pengiriman. Oleh because the authors are keen to try and retrace examine the problems of the bank interest law in the opinion of the Nahdlatul Ulama through Bahsul Masail- Her and Muhammadiyah with its Majlis Legal Affairs Committee, with a tap on the point permaslahan underlying basis of these differences regarding bank interest is through the method of taking legal keputasan drawn from the study in terms of fiqh.